1990
DOI: 10.1039/dt9900001895
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reactions of tricarbonyl[hydrotris(1-pyrazolyl)borato]rhenium(I) in the presence of neutral donor ligands. X-Ray crystal structures of the substitution derivatives [Re{HB(pz)3}(CO)2L], with L = C4H8O or PPh3

Abstract: The complex [Re{HB(pz),}(CO),][HB(pz), = hydrotris(1 -pyrazolyl)borate] has been prepared. Ultraviolet irradiation of its tetrahydrofuran (thf) solution gave [Re{H B(pz),}( CO),(thf)], which allowed the synthesis of a series of substitution derivatives [Re{HB(pz),}(CO),L],

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Recently, transition metal chemistry with hydridotris(pyrazolyl)borate ligands has attracted considerable attention. , Moret et al have reported that the tetrahydrofuran (THF) ligand of TpRe(CO) 2 (THF) ( 3 ) (Tp = hydridotris(pyrazolyl)borate) is labile, and the facile dissociation of the cyclic ether ligand allowed access to complexes of the type TpRe(CO) 2 (L) (L = PPh 3 , CH 3 CN, pyridine, and PMe 2 Ph) . To establish a benchmark for spectroscopic reference, the coordination of a nonaromatic hydrocarbon was attempted first.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, transition metal chemistry with hydridotris(pyrazolyl)borate ligands has attracted considerable attention. , Moret et al have reported that the tetrahydrofuran (THF) ligand of TpRe(CO) 2 (THF) ( 3 ) (Tp = hydridotris(pyrazolyl)borate) is labile, and the facile dissociation of the cyclic ether ligand allowed access to complexes of the type TpRe(CO) 2 (L) (L = PPh 3 , CH 3 CN, pyridine, and PMe 2 Ph) . To establish a benchmark for spectroscopic reference, the coordination of a nonaromatic hydrocarbon was attempted first.…”
Section: Resultsmentioning
confidence: 99%
“…TpRe(CO) 3 ( 2 ) and TpRe(CO) 2 (THF) ( 3 ) have been previously reported in the literature . KTp was prepared according to a published procedure …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Tp complexes have been characterized by many different methods very little is known about their electronic spectra and photochemistry. A few spectral assignments [6][7][8] and photochemical observations [9][10][11][12] have been reported. However, Tp À seems to act as a spectator ligand in these cases.…”
mentioning
confidence: 97%
“…372 The rhenium carbonyl halides [ReBr(CO) 5 ] " react with amino(imino)thiophosphoranes (R 3 C)(R 3 Si)NP(S)=NCR 3 or R(S)P(NCR 3 )SiR 2 NCR 3 to give (168) in 37% and 68% yield, respectively. 373 The tricyclic rhenium complex (169) (R = TMS) is formed in 35% yield from [ReBr(CO) 3 Rhenium complexes with tridentate nitrogen ligands have also been reported including the 1 , 4 , 7triazacyclononane ligand (172), 380 the hydrotris(l-pyrazolyl)borate ligand (173), 381 4 ] with NaBH 4 (44% yield). Treatment of the dinitrogen complex with HX gives the dihalides c/s-[Re(CO) 2 (X) 2 (r|-Cp*)], which are converted to the trans-isomevs, upon photolysis.…”
Section: Synthesis and Reactivitymentioning
confidence: 99%